Konstruksi Perilaku Keagamaan Anak Melalui Interaksi Pola Asuh Orang Tua dan Lingkungan Sosial Budaya - Heny Perbowosari; I Nyoman Kiriana (Jurnal Penelitian Agama Hindu, 2026)
Children's religious behavior is an important foundation in the formation of character and morals, which is influenced not only by internal factors, but also by the family environment and socio-cultural surroundings. In a modern context, social and cultural changes demand an understanding of how religious values are constructed from an early age. Therefore, this study aims to analyze the influence of parenting styles and the socio-cultural environment, as well as the interaction between the two, in shaping children's religious behavior. This research uses a quantitative approach with a correlational design. Data collection was carried out using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis employed multiple regression to determine the partial and simultaneous effects between variables. The findings show that children's religious behavior is formed and develops through the mutually influential relationship between parenting styles and the surrounding socio-cultural environment. Children raised with a democratic parenting style, accompanied by a religious and open environment, tend to have more moderate and tolerant attitudes, and are able to demonstrate empathy in their daily lives. In addition, the analysis also shows that the interaction between parenting styles and the socio-cultural environment plays a significant role in strengthening the internalization of religious values in children. Children who receive positive support from both aspects demonstrate consistency in practicing religious rituals, have a deeper understanding of religious teachings, and are able to adapt to evolving social dynamics. The novelty of this research lies in its integrative approach, namely by examining the interrelationship between the role of the family, local culture, and modern social dynamics simultaneously in shaping children's religious behavior. Therefore, the interaction between parenting styles and the socio-cultural environment is crucial in strengthening the internalization of religious values in children.